The Spanish of the Cantagallo Shipibo Community: An Acoustic Study of Vowel Duration - Pinillos Chávez, Paloma (2021)
This study explores the vowel duration spoken by Shipibo-Spanish bilinguals from the community of Cantagallo. This research takes into account the work of Elías Ulloa (2011), who analyzes the duration of Shipibo vowels founded on the notion of minimum word size, requirement that doesn’t exist in Spanish. Results indicate that bilingual speakers produce longer vowels than monolingual speakers. Also, vowel duration among these bilinguals varies depending on their Shipibo and Spanish dominance. On the other hand, I suggest that the nature of the long vowels produced in Spanish by Shipibo speakers could be due to the transfer of the requirement of syllabic weight from Shipibo to Spanish.